Financial Implications of Treating Breast Cancer with Standard Curative and Palliative Regimens Using the Cheapest and Costliest Branded Drugs: The First Drug Cost Analysis Study from India - Abhishek Krishna; Nikku Mathew Geevarughese; Thomas George; Manjeshwar Poonam Baliga-Rao; Princy Louis Palatty; Manjeshwar Shrinath Baliga (Journal of Radiation and Cancer Research, 2025)
Introduction: In breast cancer care, chemotherapy is an important modality, and this study evaluated the cost-minimization analysis (CMA) considering the price of the most and the least expensive branded drugs by taking body surface area (BSA) relevant to the Indian context. Objectives: The objective of this study was to conduct CMA comparing the costliest and cheapest cytotoxic drugs used to treat breast cancer in India by focusing on the direct comparison of cost. Materials and Methods: The current index of medical stores was used to identify the most and least expensive brand-name medications. Based on this, the cost difference, cost ratio, and percentage variation in cost were calculated for both individual drugs and treatment regimens. The cost of the drugs is presented in both Indian rupees and American dollars. Results: The anthracycline–taxane chemotherapy regimen with four cycles of adriamycin–cyclophosphamide + four cycles of paclitaxel had the biggest cost variation. Using a less expensive brand of trastuzumab instead of the most costly version resulted in an annual cost savings of approximately ₹715,065 ($9,608.51). Similar observations were seen for other regimens. Conclusions: A huge difference in the cost was observed between the costliest and the cheapest brands suggesting a judicious selection can reduce financial toxicity for breast cancer patients.